Mercury contamination of bottom sediments in water reservoirs of southern Poland - Koniarz, Tomasz; Tarnawski, Marek; Baran, Agnieszka; Florencka, Natalia (Geology, Geophysics and Environment, 2015)
The aim of this study was to assess the mercury concentration in bottom sediments, collected from eight reservoirs located in south-eastern Poland. A  DMA-80 Mercury Analyser was used for the analysis of the concentration of mercury in bottom sediments. Concentration of mercury in sediments was between 0.01–0.18 mg∙kg−1. The research results show that 13 samples are above the Polish Hg background level. Only 9 samples are below the background level. Generally, the sediments belonged to class I and II (unpolluted and moderately polluted sediments). The concentration of mercury in bottom sediments follows the order: Rybnik (highest) > Bagna Rzeszowskie > Rzeszów > Ożanna > Brzóza Stadnicka > Brzóza Królewska > Głuchów > Narożniki (lowest). The low mercury content in sediments is related to absent or limited anthropogenic sources of this metal. Elevated concentrations of Hg in bottom sediments of the reservoirs in Rybnik and Bagna Rzeszowskie are related to their proximity to large agglomerations and industrial plants. Organic matter was likely to be the most important factors controlling the concentration and distribution of mercury in the studied sediments.